KEPEMIMPINAN SEBAGAI DETERMINAN KINERJA KARYAWAN - Mardan, Jhonni Ardan (Komunitas Manajemen Kompetitif, 2025)
The study aims to determine the Influence of Leadership on Employee Performance. This study was conducted at the UPT. YZ. The population in this study was 91 people with a sample of 90 people. The research data were analyzed using descriptive and quantitative analysis methods. Data processing using SPSS version 25. Based on the research results at the UPT. YZ, it can be concluded that Leadership has a positive and significant effect on employee performance. This is evidenced by the simple linear regression equation Y 11.719 + 0.699X and the results of the t-test obtained a t-count value greater than the table (10.389> 1.9872) and a significance level of 0.000 less than 0.05 (0.000 <0.05). From the results of the determination test (R2) of 0.551, which means that the leadership variable has an influence of 55.1% on employee performance at the UPT. YZ. Meanwhile, the remaining 44.9% is influenced by other variable factors that were not studied